On-line scheduling of target sensitive periodic tasks with the gravitational task model - Guerra, Raphael; Fohler, Gerhard (Proceedings of the Conference on Design, Automation and Test in Europe, 2012)
Target sensitive tasks have an execution window for feasibility and must execute at a target point in time for maximum utility. In the gravitational task model, a task can express a target point, and the utility decay as a function of the deviation from this point. A method called equilibrium approximates the schedule with maximum utility accrual based on an analogy with physical pendulums. In this paper, we propose a scheduling algorithm for this task model to schedule periodic tasks. The basic idea of our solution is to combine the equilibrium with Earliest Deadline First (EDF) in order to reuse EDF's well studied timeliness analysis. We present simulation results and an example multimedia application to show the benefits of our solution.